Karakteristik Organoleptik Yoghurt Berbahan Dasar Susu Kenari - Halawane, Malpin; Tetelepta, Gilian; Tuhumury, Helen C D (Jurnal Agrosilvopasture-Tech, 2024)
This study aims to characterise the organoleptic properties of yoghurt based on the treatment of skim milk and canarium milk ratio. This study used a completely randomised design (CRD) with the treatment of skimmed milk and canarium milk ratio of 100:0, 75:25, 50:50, 25:75, 0:100. The parameters analysed were organoleptic tests including (taste, aroma, consistency, viscosity) analysed statistically. The results showed that the yoghurt tasted sour to slightly sour, flavoured sour to slightly sour, homogeneous to slightly homogeneous consistency and thick to slightly thick viscosity.